The Effect of Dorminatory Environment and Character Development on Student Motivation at Bumi Kartika Asri Jatinangor - Yuningsih, Yuningsih; Jusdijachlan, R.; Roswinna, Winna (Siber Journal of Advanced Multidisciplinary, 2024)
This Study Entitled The Influence Of Competency And Teacher Performance On Student Learning Motivation In Muhammadiyah 6 Bandung Middle School. This research is conducted on the basis that the competencies that must be possessed by the teacher as the mandate of the Law and the performance of the teacher both in educating, guiding and teaching students will have a positive impact on the formation of student motivation. The purpose of this study was to see the effect of teacher competency and performance on student learning motivation. The research method used is descriptive quantitative method as a lot of research demanded to use numbers, starting from data collection, interpretation of the data, and the appearance of the results, but in the final results a descriptive description of the final conclusions from the calculation of the numbers is clearly explained. The final results of this study are looking at the effectiveness of teacher competencies, looking at teacher performance and student motivation so far in the field. And the main outcome of this study is to see how much influence the competence and performance of teachers have on student motivation seen from the results of the analysis data using SPSS 23.